REFORMULASI PENDEKATAN PENDIDIKAN ISLAM DALAM PROBLEM KONTEMPORER - Abdul Malik (ULUL ALBAB Jurnal Studi Islam, 2016)
There are at least three crucial issues to cover in Islamic education. First is humanitarian crisis. Second, is the issue of nature. The third is the crisis of divinity. This paper aims to demonstrate that the approach developed in Islamic education contributes to solve the three major problems. The development of Islamic education curriculum should be directed to the rescue of human nature that emphasizes its approach to morality so that human are able to think and act with full of wisdom. Therefore, preparing the curriculum or Islamic education program could start from the problems faced in the community as an educational content, while the process or the learning experience is developed by studying the Quran and the hadith. Learners should be able to reflect the results of the dialogue between Quran and hadith with the reality that occurs in the community.